Philippine city disaster insurance pool rationale and design. (Asian Development Bank, 2018)
This report presents the rationale for and design of a city government disaster insurance pool in the Philippines. Insurance pools help governments enhance their financial preparedness for disasters, focusing on the provision of rapid post disaster financing for early recovery. The Philippine City Disaster Insurance Pool was developed under the guidance of the Department of Finance as part of the 2015 Disaster Risk Financing and Insurance Strategy. It utilizes a parametric insurance structure, basing payouts on the occurrence of earthquakes and typhoons according to their physical features, rather than actual losses.